Legal Remedies Against Unwanted Conduct of a Sexual Nature - Jokšaitė, Adriana; Dijokevičiūtė, Kotryna (Vilnius University Open Series, 2024)
Unwanted conduct of a sexual nature is experienced by both women and men in a variety of situations: at work, on the street, on buses, etc. Unfortunately, the legal framework for such behaviour is not clear and unambiguous, in the absence of a relationship of service or other dependence between the persons concerned. In foreign countries, unwanted conduct of a sexual nature is dealt with by strict criminal law measures. However, in Lithuania, situations of unwanted sexual conduct, where there is no element of official or other dependence between the persons concerned, are outside the scope of Article 152 of the CC. In practice, unwanted conduct of a sexual nature in everyday situations is treated as a minor public order offence under Article 481 of the ANC, which is not entirely appropriate. In the absence of an appropriate legal framework, the experience of unwanted conduct of a sexual nature in everyday situations requires consideration of criminal liability for such conduct in Lithuania. This could be achieved by removing the element of dependence from the offence under Article 152 of the CC, thus covering all situations of sexual harassment, whether on the street, on the bus or at work. A slightly milder alternative would be to consider adding a new article to the AOC with direct liability for unwanted conduct of a sexual nature (sexual harassment).